Meta-analysis of the effectiveness of the Trier Social Stress Test in eliciting physiological stress responses in children and adolescents. (June 2020) - Seddon, Jessica A.; Rodriguez, Violeta J.; Provencher, Yannick; Raftery-Helmer, Jacquelyn; Hersh, Jacqueline; Labelle, Patrick R.; Thomassin, Kristel
Highlights: TSST effectively elicits physiological and subjective stress responses in children and adolescents. TSST elicited cortisol, heart rate, pre-ejection period, heart rate variability, and systolic blood pressure reactivity. TSST also elicited negative affect and subjective anxiety. TSST reactivity for cardiac output, respiratory sinus arrhythmia, and diastolic blood pressure reactivity did not reach significance. Some physiological stress responses were moderated by sample age, gender, clinical diagnosis, and TSST modifications. Abstract: The Trier Social Stress Test (TSST) is known to reliably induce physiological stress responses in adult samples. Less is known about its effectiveness to elicit these responses in youth samples. We performed a meta-analysis of stress responses to the TSST in youth participants. Fifty-seven studies were included representing 5026 youth participants. Results indicated that the TSST was effective at eliciting stress responses for salivary cortisol (sCort; effect size [ES] = 0.47, p = 0.006), heart rate (HR; ES = 0.89, p < 0.001), pre-ejection period (PEP; ES = −0.37, p < 0.001), heart rate variability (HRV; ES = −0.33, p = 0.028), and systolic blood pressure (ES = 1.17, p < 0.001), as well as negative affect (ES = 0.57, p = 0.004) and subjective anxiety (ES = 0.80, p = 0.004) in youth samples. Cardiac output (ES = 0.15, p = 0.164), respiratory sinus arrhythmia (ES = −0.10, p = 0.064), and diastolic blood pressure (ES = 2.36, p = 0.072) did not reach statistical significance. Overall, effect sizes for the TSST varied based on the physiological marker used. In addition, several physiological markers demonstrated variance in reactivity by youth age (sCort, HR, HRV, and PEP), gender (sCort), type of sample (i.e., clinical versus community sample; sCort and HR), duration of TSST (sCort, HR, HRV, negative affect, and subjective anxiety), number of judges present in TSST (HR and subjective anxiety), gender of judges (sCort), and time of day the marker was assessed (morning versus afternoon/evening; sCort). Overall, the findings provide support for the validity of the TSST as a psychosocial stressor for inducing physiological and psychological stress responses in children and adolescents, but also highlight that some markers may capture the stress response more effectively than others.